Anti-monocyte chemoattractant protein 1 gene therapy attenuates experimental chronic pancreatitis induced by dibutyltin dichloride in rats. Issue 12 (11th November 2005) - Zhao, H F; Ito, T; Gibo, J; Kawabe, K; Oono, T; Kaku, T; Arita, Y; Zhao, Q W; Usui, M; Egashira, K; Nawata, H
Abstract : Background: Monocyte chemoattractant protein 1 (MCP-1) is a member of the C-C chemokine family and exerts strong chemoattractant activity in monocytes, macrophages, and lymphocytes. Rat pancreatic fibrosis induced by dibutyltin dichloride (DBTC) is considered to be an appropriate chronic pancreatitis model histologically and enzymatically, as has demonstrated in a previous study. Aim: We examined the effect of human dominant negative inhibitor of MCP-1 (mutant MCP-1) on progression of chronic pancreatitis induced by DBTC in a rat model. Methods: We used the experimental model of chronic pancreatitis induced by DBTC in rats. Mutant MCP-1 or empty plasmid at a dose of 50 µg/body weight was administrated into rat thigh muscles on days 4, 11, and 18 after administration of DBTC. On days 14 and 28, we evaluated the effect of mutant MCP-1 morphologically and biochemically. Results: The mutant MCP-1 treated group inhibited early pancreatic inflammation and later pancreatic fibrosis histologically, and showed a decrease in serum MCP-1 concentration, intrapancreatic hydroxyproline, α-smooth muscle actin, and an increase in intrapancreatic amylase and protein content compared with the empty plasmid treated group. The mutant MCP-1 group also inhibited intrapancreatic mRNA expression of cytokines and chemokines. Conclusions: : Our findings suggest that monocyte/macrophage recruitment and the systemic MCP-1 signal pathway contribute to progression of chronic pancreatitis, and that blockade of MCP-1 may suppress the development of pancreatic fibrosis.